Transmission of the human respiratory microbiome and antibiotic resistance genes in healthy populations - Lili Ren; Jing Yang; Yan Xiao; Li Guo; Jian Rao; Chao Wu; Xinming Wang; Ying Wang; Linfeng Zhang; Li Zhang; Xiaoqing Jiang; Jiaxin Zhong; et al. (Microbiome)
Abstract Background The human microbiome is transmissible between individuals, including pathogens and commensals with metabolic and immune-modulating effects, which could influence susceptibility, severity, and outcomes of both infection and non-infection diseases. However, limited studies of respiratory microbiome transmission within populations have been conducted. Herein, we performed species- and strain-level metagenomic analyses on oropharyngeal (OP) swabs from 1046 healthy urban dwellers across 13 districts, including 111 households with at least two cohabitants, to elucidate the transmission dynamics of the respiratory microbiome within households and communities. Results We found that geographic districts accounted for the greatest variation in the OP microbiome, with unrelated individuals from the same district showing greater microbiome similarity and higher strain-sharing rates than those from different districts. Cohabitants, especially spouses and siblings, exhibited similar microbial abundances and shared more strains, with 16.7% (IQR 0.0–33.3%) of strains shared among cohabitants, compared to 0.0% (IQR 0.0–11.1%) in non-cohabiting pairs (p < 0.05). Both respiratory commensals and opportunistic pathogens were shared among cohabitants. In contrast, no evidence of vertical transmission was detected between mother–offspring pairs. Additionally, the OP microbiome contained diverse antibiotic resistance genes (ARGs), with 15.0% linked to mobile genetic elements (MGEs) or plasmids; the flanking sequences of these ARGs were more conserved across species than those of non-MGE-associated ARGs, suggesting horizontal transfer of ARGs among respiratory microorganisms. Conclusions In summary, we characterized the transmissible nature of the OP microbiome and the risk of ARG dissemination among respiratory microorganisms. These findings underscore the role of respiratory microbes and ARGs exchange in shaping the microbiome of healthy populations and emphasize their relevance to public health strategies for respiratory health management. Video Abstract